ADAPTABILITY OF THE ACCOUNTANT PROFESSION: MENGGALI MAKNAKEBERADAAN PROFESI AKUNTAN DALAM MENAVIGASI TANTANGAN DAN MEMPERTAHANKAN RELEVANSI DI ERA TRANSFORMASI DIGITAL - Eka Putra, Moh. Rizqy; Sukma Wati, Nur; Husain, Saddan; Rismala (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2024)
This research aims to analyze the roles and functions of accountants and auditors in the context of the digital transformation era, including the challenges and opportunities they face. The research method employed is qualitative descriptive. The findings indicate that the role of the accounting profession in addressing challenges and leveraging opportunities in the digital transformation era is crucial. Accountants not only serve as conventional